Penyelesaian Sengketa Tanah Antar Warga oleh Pemerintah Desa di Desa Tainsala Kecamatan Insana Tengah Kabupaten Timor Tengah Utara - Irene Lion Sanak Email; Sukardan Aloysiu; Darius Mauritsius (International Forum of Researchers and Lecturers, 2024)
The objectives of this study are (1) To find out the factors that cause land disputes between residents in Tainsala Village (2) To find out the role of the Tainsala Village government in resolving land disputes between residents in Tainsala Village. The research method uses empirical research, namely data obtained directly from the field. This research uses empirical legal research, using a qualitative approach method, namely an approach based on the type of data and data analysis. The data used includes primary, secondary data, data collected through interviews, and non-participant observation. Also, using qualitative descriptive analysis, where the data is presented by describing the results of research on efforts to resolve land disputes between residents by the village government. The results showed: (1) Factors that cause land disputes between residents in Tainsala Village, due to unclear land ownership status, the influence of customary settlements (belis), the increasing needs of life and the high price of land and conflicts between sellers and buyers of land. (2) The role of the village government in resolving land disputes between residents in Tainsala Village, settlement by mediation, namely the village head as an arbiter in resolving disputes between two parties and settlement in a family manner, namely settlement carried out by peaceful means involving family elements from the parties to the case. The suggestions are: (1) The village government must provide direction to the community to clarify the land certificate. (2) The village government must make a statement letter if the settlement of land disputes is carried out in a family manner.